The impact of audiovisual feedback on the learning outcomes of a remote and virtual laboratory class - Lindsay, Euan; Good, M. (IEEE Education Society, 2009)
Remote and virtual laboratory classes are an increasingly prevalent alternative to traditional hands-on laboratory experiences. One of the key issues with these modes of access is the provision of adequate audiovisual (AV) feedback to the user, which can be a complicated and resource-intensive challenge. This paper reports on a comparison of two studies of remote and virtual access to hardware, one with rich AV feedback and one without. The comparison shows that the learning outcomes of the remote access mode are dependent upon the richness of the feedback; the learning outcomes of the simulated access mode are largely robust to an absence of feedback. The students' preferences are affected by the feedback, with a clear preference for richer feedback.